Dual monoclonal antibody-based sandwich ELISA for detection of in vitro packaged Ebola virus - Junjie Zai; Kai Yi; Lilan Xie; Jiping Zhu; Xiaoting Feng; Yaoming Li (BMC, 2018)
Abstract Background Rapid transmission and high mortality of Ebola virus disease (EVD) highlight a urgent need of large scale, convenient and effective measure for Ebola virus screening. Application of monoclonal antibodies (mAbs) are crucial for establishment of an enzyme-linked immunosorbent assay (ELISA) with high sensitivity and specificity. Methods The traditional cell fusion technique was used to generate a panel of hybridomas. Two mAbs were characterized by SDS-PAGE, Western blot, Indirect immunofluorescence assay (IFA). A sandwich ELISA was established using the two mAbs. The detection capability of the ELISA was evaluated. Results In the current study, we produced two murine-derived mAbs (designated as 6E3 and 3F21) towards Zaire Ebola virus glycoprotein (GP), the major viral transmembrane spike protein associated with viral attachment. It was shown that 6E3 and 3F21 recognized GP1 and GP2 subunits of the GP respectively. Furthermore, 6E3 and 3F21 bound to corresponding epitopes on GP without reciprocal topographical interpretation. Subsequently, a sandwich ELISA based on the two mAbs were established and evaluated. The detection limit was 3.6 ng/ml, with a linear range of 3.6-100 ng/ml. More importantly, Ebola virus like particles (eVLPs) were able to be detected by this established virus detection measure. Conclusions We produced and characterized two murine-derived mAbs (designated as 6E3 and 3F21) towards Zaire Ebola virus glycoprotein (GP), and established a sandwich ELISA based on the mAbs. It was suggested that the sandwich ELISA provided an alternative method for specific and sensitive detection of Ebola virus in the field setting.